Soxhlet Extraction and Characterisation of Calabash Seed Oil as an Alternative Feedstock for Aviation Biofuel Production (Unizik Journal of Chemical and Environmental Engineering, 2026)
This study investigated the potential of calabash seed oil (Lagenaria siceraria) as a sustainable feedstock for aviation biofuel production. The oil extraction process was optimised using Response Surface Methodology (RSM) based on a Central Composite Design (CCD), considering extraction temperature, extraction time, and solvent-to-solid ratio as independent variables; and oil yield as the response. Soxhlet extraction with n-hexane was employed for oil recovery, while the extracted oil was characterised through physicochemical analysis, Fourier Transform Infrared Spectroscopy (FTIR), and Gas Chromatography–Mass Spectrometry (GC–MS). The quadratic model developed for the extraction process showed high statistical significance with an R² value of 0.9691 and insignificant lack of fit of p-value, 0.2199, confirming its adequacy for predicting oil yield. The optimum extraction conditions were obtained at 60 °C, 120 min extraction time and a solvent-to-solid ratio of 80 mL/g, resulting in an experimental oil yield of 52.302%. The physicochemical properties of the oil revealed low moisture content (0.742%), low acid value (1.738 mg KOH/g), low free fatty acid content (0.869%), high flash point (289.3 °C), favourable pour point (-22.4 °C), and moderate iodine value (71.141 g I₂/100 g oil), indicating promising suitability for hydroprocessed esters and fatty acids (HEFA)-based aviation biofuel production. FTIR analysis confirmed the presence of triglycerides, ester functional groups, unsaturated fatty acids, and long-chain hydrocarbons essential for renewable jet fuel production. GC–MS analysis showed that linoleic acid (39.67%), stearic acid (21.11%), oleic acid (11.62%), and palmitic acid (10.78%) were the dominant fatty acids, demonstrating a favourable C16–C18 carbon chain distribution suitable for jet fuel-range hydrocarbon production. Although the oil exhibited relatively high viscosity and peroxide value, the overall findings suggest that calabash seed oil possesses significant potential as a non-edible, and renewable feedstock for sustainable aviation fuel production after appropriate upgrading and refining processes.
Keywords: Calabash seed oil, Aviation biofuel, Extraction, RSM, FTIR, GC-MS